Drought tolerance in popular sunflower hybrids at seedling stage - H G PRAVEEN; T K NAGARATHNA; Y A NANJA REDDY (The Indian Journal of Agricultural Sciences, 2021)
Drought is a major abiotic stress coupled with high temperature that limits the crop productivity in arid and semi-arid regions. Productivity of sunflower under moisture stress is primarily determined by seed germination and the seedling vigour for appropriate crop stand. Screening hybrids for moisture stress and high-temperature tolerance under field condition has uncertainties of uncontrolled environmental conditions and interaction of biotic and other abiotic stresses. Hence, in the present experiment, 17 popular hybrids were evaluated for moisture stress tolerance at the seedling stage using PEG-induced osmotic stress and; for high-temperature tolerance using temperature induction response (TIR) technique. The study revealed that root growth was affected higher as compared to the shoot growth in both the experiments. The shoot growth was affected higher due to high temperature as compared to the PEGinduced stress. The hybrids NDSH-1012, PSH-1962, RSFH-130, and GK-202 were tolerant to PEG induced moisture stress while, the hybrids KBSH-41, KBSH-44, KBSH-53, and SB-207 were tolerant to high temperature-induced stress. The hybrids, DRSH-1, KBSH-1 and GK-2009 were moderately tolerant for both the stresses. These hybrids are suitable for drought tolerance at seedling level. This study concludes that the evaluation of hybrids for combined stresses (drought and high temperature) would be appropriate than the individual stress in sunflower. Furthermore, hybrids tolerant to stresses at seedling level should be evaluated at later growth stages for confirmation of drought/ heat tolerance and suitable for rainfed cultivation.